(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
As the region progresses, there are many cities currently experiencing transportation problems, such as traffic congestion. In addition to traffic congestion problems, other problems that can be generated are health problems due to decreased use of active transportation such as walking and cycling. The purpose of this study is to determine the effectiveness of walking habits can improve public health status. This research uses quantitative approach with data analysis technique with Structural Equation Model (SEM). The results showed that high economic and social tends to do physical activity. The choice of residence location also gives effect to physical activity. The choice of non-motorized modes such as walking and bicycles can increase physical activity. Good and comfortable pedestrian facilities will encourage people to walk for short-distance trips, so that physical activity will increase. Increased physical activity will have a good effect on health. The travel behaviour of citizens for travel purposes will be able to reduce the risk of disease